Attitudes of cynicism, fear and acceptance with the organizational change in a group of executives in Lima (Peru). (Journal of Business, Universidad del Pacífico (Lima, Peru), 2015)
The paper analyzes, exploratory level, validation of questionnaire to measure attitudes toward organizational change proposed by the Rabelo, Ros and Torres. The study led to 23 executives in Lima, obtained high levels of reliability and validity for each of the three-dimensional model of attitudes toward organizational change proposed by the authors: "attitudes of cynicism", "attitudes of fear" and "attitudes acceptance" to organizational change. However, factor analysis of each of the three dimensions of the model identified three sub-dimensions, identifying three different groups in each dimension. Results also show that attitudes of acceptance prevail and very closely, attitudes of fear to organizational change. On a lesser extent occurs cynicism reactions. On the other hand, the cluster analysis was able to identify four executive profiles according to their behavior or attitude in organizational change: On the other hand, the cluster analysis was able to identify four executive profiles according to their behavior or attitude in organizational change: a group of executives having a harmonic pattern of cognitions and affections, with high rates of acceptance and few negative attitudes of cynicism and fears; another group of executives who have clarity and coherence of attitudes, with low levels of acceptance and many negative attitudes of fear and cynicism; and a third group of executives having a divergent pattern of attitudes.
Keywords: Organizational change management; attitude to organizational change; organizational behavior